UJI CEMARAN MIKROBA DAN CEMARAN LOGAM BOLU KUKUS BERBASIS PISANG AMBON (Musa acuminta Colla) SEBAGAI CAMILAN ALTERNATIF PADA PASIEN HIPERTENSI - Sofyan, Octa (Poltekkes Kemenkes Bengkulu, 2023)
Based on WHO data there are around 972 million people or 26.4% of people in the world who have hypertension, this number is likely to continue to increase by 29.2% in 2025. One of the steps that can reduce the prevalence of hypertension is by providing non-pharmacological therapy, one of which is the intake of bananas. Banana is a fruit that can prevent and control hypertension because it contains a lot of potassium minerals. This study aims to determine the characteristics of the test for microbial contamination and metal contamination of banana-based steamed cake. This research method uses experimental research methods. In this research, the formulation of banana-based steamed sponge cake can be used as an alternative snack for hypertension patients. The steamed sponge produced will be tested for microbial contamination and metal contamination. The analysis was carried out using the Saphiro Wilk test to see the distribution of the data, then continued with the ANOVA test for normally distributed data and the Kruskall Walis test for data that were not normally distributed. The results showed that ALT levels in formula 1 were 2,333.33 cfu/g, formula 2 was 8800 cfu/g, formula 3 was 1,566.66 cfu/g. The AKK levels in formulas 1, 2, 3 were <10 cfu/g and the Escherichia coli content in the three formulas was negative. The level of lead (Pb) in formula 1 is 0.1207 mg/kg, formula 2 is 0.1036 mg/kg, formula 3 is 0.1118 mg/kg. The level of copper (Cu) in formula 1 is 0.3243 mg/kg, formula 2 is 0.3059 mg/kg, formula 3 is 0.2897 mg/kg. The levels of zinc (Zn) in formula 1 are 1.6005 mg/kg, formula 2 is 4.6056 mg/kg, formula 3 is 3.6758 mg/kg and the arsenic content in the three formulas is negative. The conclusion in this study is that the content of microbial contamination and metal contamination of banana-based steamed sponge cake is in accordance with the SNI 01-3840 standard.